Towards a semiotic theory of style in law A Peircean approach - Bor Bettina; Könczöl Miklós (INTERNATIONAL JOURNAL OF LAW IN CONTEXT, 2019)
This paper discusses the promises and limits of a Peircean semiotic approach to the concept of style in law. It does so in two steps: first (1) by identifying the place of style within the structure of law as a system of signs, then (2) by conceptualising the link between law and style in the thought of C.S. Peirce and highlighting some of the insights from a Peircean take on legal semiotics that may contribute to our understanding of the role of style in making meaning in law. It is argued that, for a Peircean analysis of law, three levels can be distinguished, from the ‘surface structure’ down to the ‘deep structure’. It is at the middle level (that of the ‘basic structure’) that a semiotic approach can yield coherent insights in terms of style, by examining the symbols and metaphors that make for the expressibility of ‘habits’, namely experience-based patterns of action and interpretation.